A Rare Cause of Hypophosphatemia: Raine Syndrome Changing Clinical Features with Age - DAĞÇINAR, ADNAN; BEREKET, ABDULLAH; ALAVANDA, CEREN; ELÇİOĞLU, HURİYE NURSEL; ELTAN, MEHMET; ÖZTÜRK, MAKBULE NİLÜFER; SAKAR, MUSTAFA; ATA, PINAR; KAYGUSUZ, SARE BETÜL; DEMİRCİOĞLU, SERAP; KIRKGÖZ, TARIK; GÜRAN, TÜLAY; et al. (SPRINGER, 2020)
Raine Syndrome (RS) is caused by biallelic loss-of-function mutations in FAM20C gene and characterized by hypophosphatemia, typical facial and skeletal features. Subperiosteal bone formation and generalized osteosclerosis are the most common radiological findings. Here we present a new case with RS. A 9-month-old male patient on a home-type ventilator was referred for hypophosphatemia. He was born with a weight of 3800 g to non-consanguineous parents. Prenatal ultrasound had demonstrated nasal bone agenesis. A large anterior fontanel, frontal bossing, exophthalmos, hypoplastic nose, high arched palate, low set ears, triangular mouth, and corneal opacification were detected on physical examination. Serial skeletal X-rays revealed diffuse osteosclerosis at birth which was gradually decreased by the age of 5 months with subperiosteal undermineralized bone formation and medullary space of long bone could be distinguishable with bone-within-a-bone appearance. At 9 months of age, hand X-ray revealed cupping of the ulna with loose radial bone margin with minimal fraying and osteopenia. Cranial computed tomography scan showed bilateral periventricular calcification and hydrocephalus in progress. The clinical, laboratory, and radiological examinations were consistent with RS. Molecular analyses revealed a compound heterozygous mutation in FAM20C gene (a known pathogenic mutation, c.1645C > T, p.Arg549Trp; and a novel c.863 + 5 G > C variant). The patient died due to respiratory failure at 17 months of age. This case allowed us to demonstrate natural progression of skeletal features in RS. Furthermore, we have described a novel FAM20C variant causing RS. Previous literature on RS is also reviewed.
Keywords: FAM20C; Hypophosphatemia; Raine syndrome; Rickets; Osteosclerosis; Hypophosphatemic rickets; Bone; OSTEOSCLEROTIC BONE DYSPLASIA; INTRACRANIAL CALCIFICATION; HYPOPLASTIC NOSE; FAM20C GENE; MUTATIONS; PHOSPHORYLATION; DELINEATION; DEFECTS; PATIENT; CELLS